Azithromycin and Co-Trimoxazole in Antimicrobial Prophylaxis: Special Emphasis on Primary Immunodeficiencies in Children (Bangladesh Journal of Medical Science, 2021)
Patients with primary immunodeficiency diseases (PID) are prone to infectious, and they often determine the course of the disease. Antimicrobial prophylaxis for patients with PID includes co-trimoxazole, amoxicillin and macrolides. Co-trimoxazole is a widely used antimicrobial agent for pneumocystosis prophylaxis in immunocompromised patients, including patients with primary cellular immunodeficiency. Antiinflammatory effect of azithromycin made it a drug of choice in the management of chronic lung diseases in the patients with primary immunodeficiencies, especially in those with antibody deficiencies. Further randomised controlled studies are needed to define the optimal agent for all types of primary immunodeficiencies, its dose, duration of treatment, benefits and safety of long-term use.A recommendation for the prophylactic use of long-term therapy should consider the balance between benefits and risk of adverse events.Bangladesh Journal of Medical Science Vol.20(3) 2021 p.530-538